Trichoderma - The Most Widely Used Fungicide 2019
DOI: 10.5772/intechopen.84469
|View full text |Cite
|
Sign up to set email alerts
|

A Review Report on the Mechanism ofTrichodermaspp. as Biological Control Agent of the Basal Stem Rot (BSR) Disease ofElaeis guineensis

Abstract: Trichoderma spp. have been the most common fungi applied as biological control agents (BCA) as an effort to combat a wide range of plant diseases. Its uses have recorded good success rate in controlling major plant diseases. Knowledge on the mechanisms employed by Trichoderma spp. could be further studied to improve its ability as an efficient biocontrol agent. The Trichoderma ability to curb plant diseases were mainly based on the activation of single or multiple control mechanisms. It is known that the Trich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…Briefly, a 3 mm mycelium plug from a pure culture of the potential antagonistic fungus actively growing was placed next to the edge of a 60 mm PDA dish, and, on the opposite side, a similar-sized mycelial plug of the GTDs pathogen was placed. For this study, six endophytic fungi described as potential antagonists were used [29,30,[46][47][48][49]: Fusarium oxysporum, Aspergillus niger, Penicillium sp., Trichoderma sp., Clonostachys rosea, and Epicoccum nigrum, and three GTDs pathogens: Diaporthe sp., Phialophora fastigiata, and Diplodia pseudoseriata, totalizing 18 pathogen /antagonist combinations. Each combination of pathogen/antagonist was repeated 3 times as well as the controls, incubating the Petri dishes at 22 • C ± 2 • C, in dark conditions.…”
Section: Direct Inhibition Antagonism Test and Multivariate Data Anal...mentioning
confidence: 99%
“…Briefly, a 3 mm mycelium plug from a pure culture of the potential antagonistic fungus actively growing was placed next to the edge of a 60 mm PDA dish, and, on the opposite side, a similar-sized mycelial plug of the GTDs pathogen was placed. For this study, six endophytic fungi described as potential antagonists were used [29,30,[46][47][48][49]: Fusarium oxysporum, Aspergillus niger, Penicillium sp., Trichoderma sp., Clonostachys rosea, and Epicoccum nigrum, and three GTDs pathogens: Diaporthe sp., Phialophora fastigiata, and Diplodia pseudoseriata, totalizing 18 pathogen /antagonist combinations. Each combination of pathogen/antagonist was repeated 3 times as well as the controls, incubating the Petri dishes at 22 • C ± 2 • C, in dark conditions.…”
Section: Direct Inhibition Antagonism Test and Multivariate Data Anal...mentioning
confidence: 99%
“…The statements by Benhamou and Chet (1996) and Latgé (2007) were confirmed by Tapwal et al (2015), who indicate that the inhibitory power of Trichoderma species is manifested by a significant lysis of the mycelial cells of the pathogens. Nusaibah and Musa (2019), reports that Trichoderma species have the ability to attack pathogens via different modes of action. They can use the antibiotic which results from the production of substances which act as "antibiotics" and which inhibit the growth of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was also found that treatments with mixtures of BCAs and organic additives such as chitosan helped to ameliorate the effects caused by Foph through the improvement of the water potential, stomatal behavior, and biochemical expression and the decrease of vascular wilt. This response may be caused by the fact that BCAs such as T. virens may participate in the activation of single or multiple biocontrol mechanisms against plant diseases, including the production of hydrolytic enzymes such as β-1,3-glucanases, chitinases and proteases (mycoparasitism), segregation of iron-chelating siderophores to suppress pathogen growth (competition), and production of secondary metabolites for resistance induction [22,70,71]. B. velezensis can contribute to the antagonistic action against pathogens through antibiosis and direct competition for the secretion of different secondary metabolites with antibacterial and antifungal activity (lipopeptides) in the rhizosphere.…”
Section: Discussionmentioning
confidence: 99%